Relations between family cohesion and adolescent-parent’s neural synchrony in response to emotional stimulations - Deng, Xinmei; Lin, Mingping; Zhang, Lin; Li, Xiaoqing; Gao, Qiufeng (Behavioral and brain functions, 2022)
Background The interaction between parent and adolescent is more challenging than in other age periods. Family cohesion seriously impacts parent-adolescent emotional interactions. However, the underlying neural mechanism has not been fully examined. This study examined the differences in the neural synchrony in response to emotional film clips between high and low family cohesion adolescent-parent dyads by using the electroencephalograph (EEG) hyperscanning. Results Simultaneously electroencephalograph (EEG) was recorded while 15 low family cohesion parent-adolescent dyads (LFCs)and 14 high family cohesion parent-adolescent dyads (HFCs)received different emotional induction when viewing film clips. Interbrain phase-locking-value (PLV) in gamma band was used to calculate parent-adolescent dyads’ interbrain synchrony. Results showed that higher gamma interbrain synchrony was observed in the HFCs than the LFCs in the positive conditions. However, there was no significant difference between the HFCs and LFCs in other conditions. Also, the HFCs had significantly higher gamma interbrain synchrony in the positive conditions than in the negative conditions. Conclusion Interbrain synchrony may represent an underlying neural mechanism of the parent-adolescent emotional bonding, which is the core of family cohesion.